Complement Factor H Modulates Splenic B Cell Development and Limits Autoantibody Production - Kiss, Máté G.; Ozsvár-Kozma, Mária; Porsch, Florentina; Göderle, Laura; Papac-Miličević, Nikolina; Bartolini-Gritti, Barbara; Tsiantoulas, Dimitrios; Pickering, Matthew C.; Binder, Christoph J. (Frontiers in Immunology, 2019)
Complement factor H (CFH) has a pivotal role in regulating alternative complement activation through its ability to inhibit the cleavage of the central complement component C3, which links innate and humoral immunity. However, insights into the role of CFH in B cell biology are limited. Here, we demonstrate that deficiency of CFH in mice leads to altered splenic B cell development characterized by the accumulation of marginal zone (MZ) B cells. Furthermore, B cells in Cfh−/− mice exhibit enhanced B cell receptor (BCR) signaling as evaluated by increased levels of phosphorylated Bruton's tyrosine kinase (pBTK) and phosphorylated spleen tyrosine kinase (pSYK). We show that enhanced BCR activation is associated with uncontrolled C3 consumption in the spleen and elevated complement receptor 2 (CR2, also known as CD21) levels on the surface of mature splenic B cells. Moreover, aged Cfh−/− mice developed splenomegaly with distorted spleen architecture and spontaneous B cell-dependent autoimmunity characterized by germinal center hyperactivity and a marked increase in anti-double stranded DNA (dsDNA) antibodies. Taken together, our data indicate that CFH, through its function as a complement repressor, acts as a negative regulator of BCR signaling and limits autoimmunity.